Long-life proton exchange with triazole group and preparation method of long-life proton exchange
By introducing triazole groups into perfluorosulfonic acid ionic polymers, capturing or quenching free radicals, the problem of degradation of polymers under free radical attack is solved, and high chemical stability and high ion exchange capacity are achieved while simultaneously extending service life.
Patent Information
- Application Number
- CN202411398018.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2021-09-27
- Filing Date
- 2021-11-04
- Publication Date
- 2025-02-21
AI Technical Summary
Existing perfluorosulfonic acid ionic polymers are prone to degradation under the attack of free radicals, resulting in a shortened service life.
A class of perfluorosulfonic acid ionic polymers with triazole groups was designed to introduce free radically captured or quenched structural units into the polymer structure through chemical grafting to improve the chemical stability of the polymer.
It effectively weakens the degradation of polymers, improves the chemical stability and service life of perfluorosulfonic acid ionic polymers, and regulates the ion exchange capacity, meeting the requirements of high chemical stability and high ion exchange capacity.
Smart Images

Figure CN119490609A_ABST
Abstract
Description
[0001] This application is a divisional application of the application with application number 202111300385.X and invention name as perfluorosulfonic acid ion polymer with triazole group, proton membrane and membrane electrode for fuel cell and preparation method thereof Technical Field
[0002] The invention belongs to the field of fuel cell proton exchange membranes, and particularly relates to a long-life proton exchange membrane with a triazole group and a preparation method thereof. Background Art
[0003] A fuel cell is a power generation device that converts the chemical energy stored in the reactants directly into electrical energy without combustion. During operation, fuel cells do not produce nitrogen and sulfur oxides and other substances that pollute the environment, so they are considered to be an environmentally friendly device. In addition to its high energy conversion efficiency, high reliability, compressibility and good maintainability, fuel cell technology is considered to be one of the new environmentally friendly and efficient power generation technologies in the 21st century. In addition to the advantages of general fuel cells, proton exchange membrane fuel cells (PEMFC) also have the advantages of low operating temperature, fast start-up speed, light weight, long life, no corrosion and loss of electrolyte, high specific power and specific energy. PEMFC has gradually become an ideal power source for electric vehicles, mobile communications and submarines. At present, many countries in the world are promoting fuel cell transportation power solutions. In 2015, Toyota Motors of Japan sold the world's first car with PEMFC as the main power source, laying a milestone for the use of fuel cell technology in automobile power.
[0004] At present, the most representative commercial proton exchange membranes commonly used at home and abroad are the Nafion series membranes produced by DuPont in the United States in the 1980s. Nafion membranes have developed rapidly due to their excellent conductivity and good comprehensive performance and have become the standard for measuring the performance of proton exchange membranes. The main component of Nafion membrane is perfluorosulfonic acid ionomer (PFSIs), whose polymer chain has an ultra-stable perfluoro backbone skeleton -(CF2CF2)m-(CF2CF)n- and a side chain with a sulfonic acid group (-SO3H) as the end group, so it has high chemical stability and good thermal stability. The perfluorosulfonic acid proton exchange membrane prepared by PFSIs has been widely concerned because of its high chemical stability, high conductivity under high humidity, high current density at low temperature, and low resistance. The chemical stability of perfluorosulfonic acid polymers directly determines the long-term operation life of fuel cells. However, during the operation of fuel cells, the -SO3H side groups carried by perfluorosulfonic acid polymers are easily attacked by hydroxyl radicals, and ultimately lead to zipper-like degradation of the polymer backbone. Therefore, improving the chemical stability of PFSIs is of great significance to the industrial development of fuel cells.
[0005] Current research believes that the chemical degradation process of PFSIs is mainly: during the synthesis of perfluoropolymers, the initiator will inevitably produce unstable groups such as -CF=CF2, -COOH, -CF2SO3H and -CF2H at the end of the molecular chain, and the free radicals (HO·&HOO·) attack the unstable groups at the end of the molecular chain, resulting in the "zipper-like" degradation of the polymer. Therefore, designing and synthesizing PFSIs with high chemical stability has become a very important topic. At present, the means to improve the chemical stability of PFSIs mainly include: (1) inhibiting the generation of free radicals during the application of polymers, such as Chinese patent document CN112436170A, adding additives that can scavenge free radicals to the perfluorosulfonic acid proton exchange membrane to capture the free radicals in the system, thereby alleviating their attack on the proton exchange membrane and increasing the chemical stability of the membrane; (2) using the optimization of the polymer structure to quench or capture the generated free radicals, such as Chinese patent document CN 102479956A introducing Zr into the perfluorosulfonic acid proton exchange membrane by ion exchange method 4+ , Ca 2+ Mg 2+ 、Al 3+ One or more metal ions in the proton exchange membrane are added to modify the microscopic morphology of the proton exchange membrane, which greatly improves the chemical stability of the membrane. The above methods all require the polymer to be prepared into a proton membrane, and then post-treatment measures are taken on the proton membrane to resist the attack of free radicals. These methods do not take measures to quench or capture the generated free radicals at the source of the polymer and its synthesis process, and additives or dopants are easily lost from the proton exchange membrane. Therefore, it is of great significance to synthesize PFSIs with high chemical stability by optimizing and modifying the polymer molecular chain to extend the service life of the proton exchange membrane. Summary of the invention
[0006] In order to solve the problem that the existing perfluorosulfonic acid ion polymers are easily degraded under the attack of free radicals, thereby shortening the service life, the present invention provides a type of perfluorosulfonic acid ion polymer with a triazole group and a preparation method thereof. The chemical structure of the perfluorosulfonic acid ion polymer retains the structural advantages of the perfluorosulfonyl fluoride resin, and at the same time, a free radical capture or quenching structure (triazole structural unit) is introduced into the structure by chemical grafting, which can fundamentally achieve the purpose of polymer resistance to free radical attack, effectively reduce the degradation of the polymer, and thus improve the chemical stability of the perfluorosulfonic acid ion polymer. In addition, the triazole structural unit introduced into the obtained polymer structure can regulate the ion exchange capacity (IEC) of PFSIs, so that the obtained PFSIs can simultaneously achieve the purpose of effectively regulating IEC and chemical stability.
[0007] The present invention also provides a proton membrane for a fuel cell. The proton membrane is prepared from the above-mentioned perfluorosulfonic acid ion polymer and has high mechanical strength and thermal stability. Functional triazole groups are introduced into the structure of the proton membrane to regulate the ionic conductivity of the proton membrane, effectively capture or quench free radicals, thereby weakening or slowing down the degradation of the proton membrane and extending its service life.
[0008] The present invention also provides a membrane electrode, the catalyst layer of which contains the above-mentioned perfluorosulfonic acid ion polymer with triazole groups, which can effectively capture or quench free radicals, improve the stability of the membrane electrode, and extend its service life.
[0009] In order to achieve the above object, the present invention adopts the following technical solutions:
[0010] 1. A perfluorosulfonic acid ion polymer with a triazole group, the molecular structure of the polymer is shown in formula (I):
[0011]
[0012] The polymer chain structure of formula (I) comprises (A) unit and (B) unit, wherein (A) unit is a triazole structural unit, (A) unit comprises a triazole group M and a perfluoroether structural unit, and (B) unit comprises an ionic group -SO3H and a perfluoroether structural unit;
[0013] In the structure of formula (I), m is an integer of 0 to 10, preferably, m is an integer of 1 to 3; n is an integer of 1 to 6, preferably, n is an integer of 1 to 3; more preferably, m=1, n=2;
[0014] In the structure of formula (I), x is an integer of 1-30, x+y / (x+y+z)=0.05-0.8, preferably, x+y / (x+y+z)=0.15-0.4; y / (y+z)=0.2-0.6, preferably, y / (y+z)=0.2-0.4;
[0015] The structural formula of the reagent providing the triazole group M in the (A) unit is shown in formula (II),
[0016]
[0017]
[0018] In formula (II), R1 to R9 groups are any one of -H, -NH2, -PhNH2, -Cl, -Br, -PhCOOH, -CH3, -Ph (Ph represents a benzene ring), -O-CH3, and -NO2;
[0019] Among the R1 to R9 groups, at least one group contains -NH2, and the other groups are electron-withdrawing groups, electron-donating groups or -H, and the number of electron-withdrawing groups is at most 3;
[0020] Among them, the electron-donating groups in the above groups include: -NH2, -Ph, -PhNH2, -PhCOOH, -O-CH3, -CH3; the electron-withdrawing groups include -Cl, -Br, -NO2;
[0021] The order of electron-withdrawing ability of the above electron-withdrawing groups is: -NO2>-Cl>-Br.
[0022] In the present invention, the electron-donating group is beneficial to form a conjugated system with the triazole group, and can combine with free radicals to extend the life of the perfluoro ion polymer.
[0023] Preferably, the number of -NH2 contained in R1 to R9 is at most 3;
[0024] Preferably, R1 is -H, -NH2, -PhNH2, -Cl, -Br, -PhCOOH, -CH3, -Ph (Ph represents a benzene ring) or -O-CH3;
[0025] R2 is -H, -NH2, -PhNH2, -Cl, -PhCOOH or -CH3;
[0026] R3 is -H, -NH2, -PhNH2, -Br, -PhCOOH, -CH3 or -Ph;
[0027] R4 is -H, -NH2, -PhNH2, -Br, -PhCOOH, -CH3 or -Ph;
[0028] R5 is -H, -NH2, -PhNH2, -Br or -CH3;
[0029] R6 is -H, -NH2, -PhNH2, -Cl, -Br, -CH3 or -O-CH3;
[0030] R7 is -H, -NH2, -PhNH2, -Br, -CH3 or -NO2;
[0031] R8 is -H, -NH2, -PhNH2, -Br, -CH3 or -NO2;
[0032] R9 is -H, -NH2, -PhNH2, -Cl, -Br, -CH3 or -Ph.
[0033] Further preferably, R1 and R2 are respectively one of -NH2, -H, and -PhNH2; R3 and R4 are respectively one of -H, -NH2, -PhNH2, and -CH3; R5 and R8 are respectively one of -H, -NH2, and -CH3; R6 and R9 are respectively one of -H, -NH2, and -PhNH2; R7 is one of -H, -NH2, and -NO2;
[0034] In at least one preferred technical solution of the present invention, R1 is -NH2, and R2 to R9 are all -H.
[0035] The number average molecular weight of the perfluorosulfonic acid ionomer in the formula (I) is 200,000 to 1,000,000, preferably 200,000 to 600,000, and more preferably 300,000 to 500,000.
[0036] The perfluorosulfonic acid ion polymer has the following advantages: retaining the ultra-stable advantageous unit of the perfluoropolymer - (CF2CF2) x -, ensuring sufficient mechanical strength and thermal stability of the polymer; using the PFSIs side chain end group for chemical grafting, the introduced functional triazole structural unit can effectively capture or quench free radicals, thereby weakening or slowing down the degradation of the polymer; the perfluoroionic polymer synthesized by the present invention can simultaneously meet the requirements of high ion exchange capacity (IEC) and strong chemical stability, and has wide application. By adjusting the proportion of triazole structural units, i.e., the grafting rate, IEC and chemically stable PFSIs that meet various requirements can be synthesized;
[0037] 2. The preparation method of the above-mentioned perfluorosulfonic acid ionomer with triazole group comprises the following steps:
[0038] (1) selecting a perfluorosulfonyl fluoride resin (III) and a reagent containing a triazole group M to undergo a one-step grafting reaction in an organic solvent to synthesize an intermediate product (IV);
[0039] Alternatively, the perfluorosulfonyl fluoride resin (III) is pre-swelled in an organic solvent and then grafted with a reagent containing a triazole group M to synthesize an intermediate product (IV);
[0040] The reaction formula is as follows:
[0041]
[0042] (2) The intermediate product (IV) obtained in step (1) is treated with alkali and acid successively to complete ion exchange, and the unreacted sulfonyl fluoride group (-SO2F) is converted into a perfluorosulfonic acid group (-SO3H), and after washing and drying, a perfluorosulfonic acid ion polymer (I) with a triazole group is obtained. The reaction formula is as follows:
[0043]
[0044] Preferably, the organic solvent in step (1) is at least one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, ethanol, isopropanol, dimethyl sulfoxide or ethyl acetate.
[0045] Preferably, in the structural formula (III) of the perfluorosulfonyl fluoride resin polymer chain in step (1), m=1-3, n=1-3, x is an integer of 1-15, and the number average molecular weight is 250,000-500,000; further preferably, m=1, n=2, x is 10, and the number average molecular weight is 350,000-500,000.
[0046] Preferably, in step (1), the molar ratio of the perfluorosulfonyl fluoride resin to the reagent containing the triazole group M is 1:3-10.
[0047] Preferably, the mass volume ratio of the perfluorosulfonyl fluoride resin to the organic solvent in step (1) is 1:1 to 30, g / mL; more preferably 1:1 to 20, g / mL; most preferably 1:1 to 10, g / mL.
[0048] Preferably, the grafting reaction temperature in step (1) is 15 to 150° C., more preferably 25 to 80° C., and the reaction time is 1 to 48 hours, more preferably 8 to 12 hours.
[0049] Preferably, the pre-swelling in step (1) is to swell the perfluorosulfonyl fluoride resin in an organic solvent at 40 to 80° C. for 60 to 100 minutes.
[0050] Preferably, the base in step (2) is one of sodium hydroxide and potassium hydroxide, and the concentration is 5-50wt%, more preferably 15-40wt% of sodium hydroxide, and the acid is one of hydrochloric acid, sulfuric acid and nitric acid, and the concentration is 5-50wt%, more preferably 25-40wt% of sulfuric acid or nitric acid.
[0051] Preferably, the washing in step (2) is performed with deionized water, and the drying is performed at 55 to 65° C. for 18 to 36 hours.
[0052] The ion exchange capacity (IEC) and the proportion of triazole structural units (grafting rate) of the perfluorosulfonic acid ion polymer (I) prepared by the above method are determined by acid-base titration. According to the product performance requirements, the grafting rate of the polymer can be regulated by regulating the reaction time and reaction temperature in step (1), thereby regulating the IEC of the perfluorosulfonic acid ion polymer (I) and the proportion of triazole structural units.
[0053] 3. Application of the above-mentioned perfluorosulfonic acid ion polymer (I) with triazole groups in one or more of the following: 1) Application in the manufacture of ion exchange membranes in fuel cells or electrolysis devices; 2) Application as a superacid in chemical catalysis; 3) Application in electrodialysis; 4) Application in seawater desalination; 5) Application in gas separation; 6) Application in the preparation of membrane electrodes for fuel cells; 7) Application in sewage treatment.
[0054] 4. The present invention also provides a proton membrane for a fuel cell, wherein the proton membrane component includes the above-mentioned perfluorosulfonic acid ion polymer with triazole groups.
[0055] The structure of the proton membrane is selected from one of the following:
[0056] 1) Proton membrane prepared from the above-mentioned perfluorosulfonic acid ionomer with triazole groups;
[0057] 2) A composite proton membrane formed by a mixture of the above-mentioned perfluorosulfonic acid ion polymer with triazole groups and a perfluorosulfonic acid polymer.
[0058] Preferably according to the present invention, the ion exchange capacity of the proton membrane is 0.9-1.25 mmol / g, the ion conductivity is 50-200 mS / cm, the thermal degradation temperature is 280-320°C, and after 200h of Fenton test, the ion exchange capacity retention rate is above 94%, and the ion conductivity retention rate is above 93%.
[0059] Preferably, the proton membrane has a thickness of 10-200 μm.
[0060] 5. The method for preparing the proton membrane for fuel cell comprises the following steps:
[0061] The perfluorosulfonic acid ion polymer with triazole groups is dissolved in an organic solvent to prepare a perfluorosulfonic acid ion polymer solution, and a proton membrane is directly prepared using the perfluorosulfonic acid ion polymer solution;
[0062] Alternatively, the perfluorosulfonic acid ion polymer is added as a free radical quencher to a conventional perfluorosulfonic acid resin solution to obtain a polymer composite solution, and the composite proton membrane is prepared using the polymer composite solution;
[0063] Methods for preparing proton membranes using polymer solutions include spin coating, screen printing, dip coating, inkjet printing, solution casting, spray pyrolysis, etc., with solution casting being preferred.
[0064] Preferably, the concentration of the perfluorosulfonic acid ion polymer solution is 2-35 wt %, preferably 5-30 wt %.
[0065] Preferably, the organic solvent is at least one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, ethanol, isopropanol, ethanol / water mixed solvent, isopropanol / water mixed solvent, dimethyl sulfoxide or ethyl acetate.
[0066] Preferably, the volume ratio of ethanol to water in the perfluorosulfonic acid ion polymer solution is 8-9:1-2, and the volume ratio of isopropanol to water is 8-9:1-2.
[0067] Preferably, the total concentration of polymers in the polymer composite solution is 5 to 30%.
[0068] Preferably, the steps of the solution casting method are:
[0069] The perfluorosulfonic acid ion polymer solution or polymer composite solution is coated on a quartz surface dish, pre-dried at 80-90° C., dried at 140-150° C. for 90-100 minutes, and then removed from the mold.
[0070] In the present invention, when preparing the proton membrane, the conductivity, chemical stability and life of the proton membrane can be controlled by adjusting the mass fraction of the perfluorosulfonic acid ion polymer with triazole groups according to the product performance requirements.
[0071] 6. The present invention also provides a membrane electrode for a free radical resistant fuel cell, wherein the catalyst mixture component of the catalyst layer of the membrane electrode comprises the above-mentioned perfluorosulfonic acid ion polymer with triazole groups;
[0072] The membrane electrode for the anti-free radical fuel cell is composed of an electrode layer and a proton membrane, wherein the electrode layer includes a gas diffusion layer and a catalyst layer, the electrode layer is divided into a hydrogen electrode and an oxygen electrode, and the proton membrane is located between the hydrogen electrode and the oxygen electrode;
[0073] The above-mentioned proton membrane can be the above-mentioned proton membrane for fuel cells of the present invention or other conventional proton membranes for fuel cells;
[0074] The duration of the membrane electrode at an open circuit voltage of 0.9-1.2V, a relative humidity of 30% and a temperature of 90°C is greater than 200h.
[0075] 7. The method for preparing the above-mentioned membrane electrode for anti-free radical fuel cell comprises the following steps:
[0076] (1) dissolving the above-mentioned perfluorosulfonic acid ion polymer with triazole groups in a water / alcohol mixed solvent to prepare a perfluoro ion polymer solution or adding the obtained perfluoro ion polymer solution to a conventional perfluorosulfonic acid resin solution to prepare a perfluoro ion polymer composite solution, then adding a Pt / C platinum-based catalyst to the perfluoro ion polymer solution or the perfluoro ion polymer composite solution, and ultrasonically obtaining a membrane electrode slurry;
[0077] (2) using a spray gun to spray the membrane electrode slurry onto the hydrophobic treated gas diffusion layer to form a catalyst layer, and after heat treatment to obtain an electrode layer consisting of the gas diffusion layer and the catalyst layer, the obtained electrode layer is divided into a hydrogen electrode and an oxygen electrode;
[0078] (3) The hydrogen electrode and oxygen electrode cut to appropriate sizes are placed on the upper and lower sides of the proton exchange membrane, aligned and matched perfectly, and the membrane electrode is obtained after hot pressing by a press and natural cooling.
[0079] The gas diffusion layer consists of a base layer and a microporous layer, wherein the base layer material is mostly porous carbon paper or carbon cloth, and the microporous layer is usually composed of conductive carbon black and a hydrophobic agent. The base layer is composed of a porous, non-woven carbon substrate with a macroporous structure. After the substrate is treated with PTFE hydrophobicity, a single or multi-layer microporous layer (MPL) is coated to form a porous structure with different pores.
[0080] Preferably, the alcohol in the water / alcohol mixed solvent in step (1) is ethanol or isopropanol, and the volume ratio of water to alcohol is 1-2:8-9.
[0081] Preferably, the concentration of the perfluorosulfonic acid ion polymer with triazole groups in the polymer composite solution in step (1) is 5 to 15 wt %.
[0082] Preferably, the ultrasonic time in step (1) is 30 to 200 minutes.
[0083] Preferably, the platinum loading of the catalyst layer in step (2) is 0.35-0.45 mg / cm 2 .
[0084] Preferably, the gas diffusion layer in step (2) is carbon paper treated with PTFE hydrophobicity.
[0085] Preferably, the heat treatment process in step (2) is heat treatment at 80-130° C. for 30-200 min.
[0086] Preferably, in step (3), the pressure of the hot pressing treatment in the press is 0.1 to 5 MPa, the hot pressing temperature is 80 to 140° C., and the duration is 30 to 150 seconds.
[0087] Preferably, the proton exchange membrane in step (3) may be the proton membrane for fuel cell of the present invention or other conventional proton membrane for fuel cell.
[0088] In the present invention, when preparing a membrane electrode for a fuel cell, the chemical stability of the membrane electrode for the fuel cell can be regulated by adjusting the proportion of the perfluorosulfonic acid ion polymer with a triazole group according to the requirements of product performance, thereby regulating the length of its service life.
[0089] One or more technical solutions provided by the embodiments of the present invention have at least the following technical effects:
[0090] (1) The perfluorosulfonic acid ionomer with triazole groups in the present invention retains the ultra-stable main chain of the perfluoropolymer - (CF2CF2) x -, can ensure that the polymer has sufficient mechanical strength and thermal stability;
[0091] (2) The perfluorosulfonic acid ionomer with triazole groups in the present invention has triazole groups in the side chains of the molecular chains, which can effectively capture or quench free radicals, thereby weakening or slowing down the degradation of the polymer and improving the chemical stability and life of the polymer;
[0092] (3) The present invention can achieve the technical effect of regulating the ion exchange capacity, chemical stability and service life of the target polymer by regulating the grafting rate;
[0093] (4) The polymer molecular chain side chain constituting the proton membrane of the present invention is grafted with a triazole group, which has the function of resisting free radical attack, can weaken or slow down the degradation of the proton membrane, and prolong the service life of the proton membrane;
[0094] (5) The catalyst layer of the membrane electrode in the present invention comprises a perfluorosulfonic acid ion polymer with a triazole group, which has a high ability to resist free radical attack and can extend the service life of the membrane electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0095] Figure 1 This is the infrared characterization result diagram of the target product A1 in Example 1.
[0096] Figure 2 This is a graph showing the conductivity retention rate of the proton membrane for the fuel cell in Example 2 from 0 to 115 days.
[0097] Figure 3 This is a graph showing the IEC retention rate of the target product A2 in Example 1 from 0 to 115 days. DETAILED DESCRIPTION
[0098] The present invention will be further described below with reference to specific embodiments, but is not limited thereto.
[0099] It should be noted that the experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents, materials and equipment described are all commercially available unless otherwise specified.
[0100] The target polymer and perfluorosulfonic acid resin in the examples were subjected to Fenton tests respectively to accelerate the oxidation of the target polymer and perfluorosulfonic acid resin to achieve the purpose of examining their chemical stability. The chemical stability of the polymer was evaluated by testing the retention rate (RV%) of the IEC of the polymer before and after the Fenton test.
[0101] Fenton experimental method: Add ferrous ion solution to 30wt% H2O2 solution to make Fe 2+ The concentration is 20ppm, and the Fenton reagent is prepared. The object to be tested is immersed in the Fenton reagent in a water bath at 80℃. After soaking for a certain period of time, the IEC of the polymer is tested to determine the chemical stability of the polymer. In order to ensure the concentration of hydroxyl radicals, the Fenton reagent needs to be replaced every 3 hours.
[0102] Titration of ion exchange capacity IEC: accurately weigh a certain weight of dry polymer resin, then treat it in deionized water at 80℃ for 1 hour, and use a 1M NaCl aqueous solution for ion exchange for more than 12 hours. Collect the exchanged solution, use phenolphthalein as an indicator, and titrate with 0.1M NaOH standard solution until the solution turns pink. The IEC value of the polymer can be calculated according to the following formula:
[0103] IEC=(V NaOH ×c NaOH ) / m
[0104] Where:
[0105] V NaOH ——The volume of NaOH solution consumed, in mL,
[0106] c NaOH ——The molar concentration of NaOH solution, in mmol / mL,
[0107] m – mass of dry polymer resin, in g.
[0108] Retention rate of ion exchange capacity IEC:
[0109] RV%=(IEC1-IEC0) / IEC0
[0110] Where:
[0111] IEC1 and IEC0 represent the ion exchange capacity of the target product before and after the Fenton experiment, respectively.
[0112] Proton membrane ion conductivity determination: The proton membrane resistance R was tested by the two-electrode method, the instrument used was the electrochemical workstation Autolab PGSTA302, the frequency range was 106Hz-10Hz, and the conductivity was calculated by the calculation formula:
[0113] σ=L / RS
[0114] Where:
[0115] L is the thickness of the membrane (cm), R is the resistance of the membrane (Ω), σ is the conductivity of the sample (S / cm), and S is the test area of the sample (cm 2 ).
[0116] Retention rate of proton membrane ion conductivity:
[0117] RV%=(σ1-σ0) / σ0
[0118] Where:
[0119] σ0 and σ1 represent the ionic conductivity of the proton membrane before and after the Fenton experiment, respectively.
[0120] Thermal degradation temperature (defined as the temperature at which the polymer degrades 5%): The test was conducted using a thermogravimetric analyzer, TAQ50 produced by Perkin Elmer, USA, with a N2 atmosphere, a heating rate of 10°C / min, and a temperature range of 50-800°C. The samples were dried at 60°C for 24 hours before testing.
[0121] Membrane electrode durability test:
[0122] The durability or chemical stability of the membrane electrode samples was evaluated at open circuit voltage (OCV) at 30% relative humidity (RH) and 90°C, with hydrogen and air gas flow rates of 3.43 slpm and 8.37 slpm, respectively. The OCV of each cell in the stack was monitored over time. When the OCV of any of the five cells in the stack reached 0.8 V or the H2Crosover was greater than 10 mA / cm 2 , end the test.
[0123] Example 1
[0124] A long-life perfluorosulfonic acid polymer with triazole groups and a preparation method thereof, the specific preparation method is as follows:
[0125] 4-amino-3,5-di-2-pyridyl-4H-1,2,4-triazole was selected as a reagent with a triazole group (R1 is -NH2, R2-R9 are all H) and reacted with a perfluorovinylsulfonyl fluoride resin (m=1, n=2, number average molecular weight of 420,000, x value of 10) to synthesize the target product. The specific steps are as follows:
[0126] (1) After cleaning a 150 mL reaction kettle, add 30 g of perfluorovinylsulfonyl fluoride resin to 50 mL of N, N-dimethylformamide, turn on the stirring device, heat to 60 ° C, and pre-swell for 60 minutes. After vacuuming and replacing with high-purity nitrogen three times, add 0.15 g of 4-amino-3,5-di-2-pyridyl-4H-1,2,4-triazole, wait for it to completely dissolve, slowly heat to 80 ° C and react. The molar ratio of perfluorovinylsulfonyl fluoride resin to 4-amino-3,5-di-2-pyridyl-4H-1,2,4-triazole is about 1:9.8. Under mechanical stirring at 80 ° C (N2 environment), reflux reaction for 10 hours, cool to room temperature, filter the product, wash it with ethanol and deionized water for many times to remove unreacted 4-amino-3,5-di-2-pyridyl-4H-1,2,4-triazole, and dry it to obtain an intermediate product, which is recorded as A1. The reaction formula is as follows:
[0127]
[0128] The intermediate product A1 was subjected to infrared transmission spectrum measurement, and the test results were as follows: Figure 1 As shown in Figure 2, after the reaction, A1 still retains the sulfonyl fluoride group (-SO2F) in the perfluorosulfonyl fluoride resin, and its characteristic peak is at 1467 cm -1 Nearby, the characteristic peaks of the C=N double bond in the triazole structural unit, the S-N bond of the connecting group, and the NH bond appeared at the same time, and their characteristic peaks were at 1670 cm -1 、1398cm -1 and 3500cm -1 Nearby; infrared results proved that intermediate product A1 has been successfully synthesized;
[0129] (2) The intermediate product A1 obtained in step (1) is treated with 30 wt % sodium hydroxide and 25 wt % sulfuric acid to complete ion exchange, and all unreacted sulfonyl fluoride groups (-SO2F) are converted into perfluorosulfonic acid groups (-SO3H). The product is washed with deionized water for multiple times and dried at 60° C. for 24 h to obtain the target product, which is denoted as A2. Its ion exchange capacity can be determined by titration. The reaction formula is as follows:
[0130]
[0131] The stability of the target product A2 was tested by Fenton test. Figure 3 As shown, after 115 days of free radical decay test, the ion exchange capacity (IEC) retention rate is as high as more than 90%, which proves that the obtained perfluorosulfonic acid ion polymer has a high ability to resist free radical attack and can effectively improve the service life of the perfluorosulfonic acid ion polymer.
[0132] According to Fourier transform infrared spectroscopy and IEC determination, y / (y+z)=0.28 in the obtained A2 polymer structure, and the IEC of the obtained target product A2 is 1.06 mmol / g.
[0133] Example 2
[0134] A proton membrane for a fuel cell and a preparation method thereof, the preparation steps are as follows:
[0135] The target product A2 prepared in Example 1 was dissolved in N,N-dimethylformamide to prepare a 15 wt% polymer solution, and then the solution was coated on a clean and smooth quartz surface dish, pre-dried at 80°C, placed in an oven at 145°C for 90 minutes, taken out and demolded to prepare a long-life perfluorosulfonic acid proton membrane.
[0136] The ion exchange capacity IEC of the proton membrane was measured by titration and was found to be 1.06 mmol / g.
[0137] The ionic conductivity of the proton membrane in deionized water at 25° C. is 80 mS / cm, and the conductivity described in the present invention is measured under this condition.
[0138] The stability of the above proton membrane was tested by Fenton test. The results are as follows: Figure 2 As shown, after 115 days of free radical decay test, the ion conductivity retention rate of the proton membrane is as high as over 90%, which proves that the obtained proton membrane has a high ability to resist free radical attack and can effectively improve the service life of the proton membrane.
[0139] Example 3
[0140] A perfluorosulfonic acid ionomer with a triazole group and a preparation method thereof, the specific preparation method is as follows:
[0141] 4-amino-3,5-di-2-pyridyl-4H-1,2,4-triazole was selected as a reagent with a triazole group (R1-NH2, R2-R9 are all -H) and reacted with a perfluorovinylsulfonyl fluoride resin (m=0, n=2, number average molecular weight of 420,000, x value of 8) to synthesize the target product. The specific steps are as follows:
[0142] (1) After cleaning a 150 mL reactor, add 10 mL of N, N-dimethylformamide, turn on the stirring device, evacuate and replace with high-purity nitrogen three times, add 0.15 g of 4-amino-3,5-di-2-pyridyl-4H-1,2,4-triazole, slowly heat to 80°C, and add 30 g of perfluorovinylsulfonyl fluoride resin after it is completely dissolved. The molar ratio of perfluorovinylsulfonyl fluoride resin to 4-amino-3,5-di-2-pyridyl-4H-1,2,4-triazole is about 1:9.8. Under mechanical stirring at 80°C (N2 environment), reflux reaction for 24 hours, cool to room temperature, filter the product, wash with ethanol and deionized water for many times to remove unreacted 4-amino-3,5-di-2-pyridyl-4H-1,2,4-triazole, and dry to obtain an intermediate product, which is recorded as A3. The reaction formula is as follows:
[0143]
[0144] (2) The intermediate product A3 obtained in step (1) is treated with 30 wt % sodium hydroxide and 25 wt % sulfuric acid respectively to complete ion exchange, and all unreacted sulfonyl fluoride groups (-SO2F) are converted into perfluorosulfonic acid groups (-SO3H). The product is washed with deionized water for multiple times and dried at 60° C. for 24 h to obtain the target product, which is denoted as A4. Its ion exchange capacity can be determined by titration. The reaction process is as follows:
[0145]
[0146] According to IEC measurement, y / (y+z)=0.30 in the obtained A4 polymer structure, and the IEC of the obtained A4 polymer is 1.26 mmol / g.
[0147] Example 4
[0148] A proton membrane for a fuel cell and a preparation method thereof, the specific preparation steps are as follows:
[0149] The target product A4 obtained in Example 3 was dissolved in a mixed solvent of isopropanol / water (volume ratio = 8:2) to prepare a 20wt% perfluorosulfonic acid ion polymer solution, and then the solution was coated on a clean and smooth quartz surface dish, pre-dried at 80°C, placed in an oven at 145°C for 90 minutes, and removed from the mold to prepare a long-life perfluorosulfonic acid proton membrane. The ion conductivity of the obtained proton membrane was 105mS / cm.
[0150] The ion exchange capacity IEC of the above proton membrane is 1.26 mmol / g as determined by titration.
[0151] Example 5
[0152] A perfluorosulfonic acid ionomer with a triazole group and a preparation method thereof, the specific implementation method is as follows:
[0153] 4-Amino-3,5-di-2-pyridyl-4H-1,2,4-triazole was selected as a reagent with a triazole group (R1-NH2, R2-R9 are all -H) and reacted with perfluorovinylsulfonyl fluoride resin (m=0, n=4, number average molecular weight of 420,000, x value of 10) to synthesize the target product. The specific experimental steps are as follows:
[0154] (1) After cleaning a 150 mL reactor, add 100 mL of N, N-dimethylacetamide, turn on the stirring device, evacuate and replace with high-purity nitrogen three times, add 0.15 g of 4-amino-3,5-di-2-pyridyl-4H-1,2,4-triazole, slowly heat to 80°C, and add 30 g of perfluorovinylsulfonyl fluoride resin after it is completely dissolved. The molar ratio of perfluorovinylsulfonyl fluoride resin to 4-amino-3,5-di-2-pyridyl-4H-1,2,4-triazole is about 1:9.8. Under mechanical stirring at 80°C (N2 environment), reflux reaction is carried out for 30 hours, then cooled to room temperature, the product is filtered, washed with ethanol and deionized water for multiple times to remove unreacted 4-amino-3,5-di-2-pyridyl-4H-1,2,4-triazole, and dried to obtain an intermediate product, which is recorded as A5. The reaction process is as follows:
[0155]
[0156] (2) The intermediate product A5 obtained in step (1) is treated with 30 wt % sodium hydroxide and 25 wt % sulfuric acid to complete ion exchange, and all unreacted sulfonyl fluoride groups (-SO2F) are converted into perfluorosulfonic acid groups (-SO3H). The product is washed with deionized water for multiple times and dried at 60° C. for 24 h to obtain the target product, which is denoted as A6. Its ion exchange capacity can be determined by titration. The reaction process is as follows:
[0157]
[0158] According to infrared spectrum and IEC determination, the IEC of the obtained target product A6 is 1.16 mmol / g, and y / (y+z)=0.32 in the obtained A6 polymer structure.
[0159] Example 6
[0160] A proton membrane for a fuel cell and a preparation method thereof, the specific preparation steps are as follows:
[0161] The target product A6 prepared in Example 5 was dissolved in a mixed solvent of ethanol / water (volume ratio = 9:1) to prepare a 15wt% polymer solution, and then the solution was coated on a clean and smooth quartz surface dish, pre-dried at 80°C, placed in an oven at 145°C for 90 minutes, and removed from the mold to prepare a long-life perfluorosulfonic acid proton membrane. The ion conductivity of the proton membrane was 90mS / cm.
[0162] The ion exchange capacity IEC of the proton membrane was measured by titration and was 1.16 mmol / g.
[0163] Example 7
[0164] A fuel cell composite proton membrane of a perfluorosulfonic acid polymer with a triazole group and a preparation method thereof, comprising the following steps:
[0165] (1) The target product A2 obtained in Example 1 was dissolved in a mixed solvent of isopropanol / water (volume ratio = 8:2) to prepare a 20 wt % polymer solution A7.
[0166] (2) Take perfluorosulfonic acid resin (V) (whose number average molecular weight is 400,000; ion exchange capacity is 0.95 mmol / g, structural formula is shown below, a value is 10), whose structural formula is as follows, and dissolve it in a mixed solvent of isopropanol / water (volume ratio = 8:2) to prepare a 20 wt% polymer solution A8.
[0167]
[0168] (3) Solution A7 was added to solution A8 and mixed evenly by mechanical stirring, and the mass ratio of the two was 1:9. The obtained mixed solution was coated on a clean and smooth quartz surface dish, pre-dried at 80°C, placed in an oven at 145°C for 90 minutes, and removed from the mold to prepare a long-life perfluorosulfonic acid composite proton membrane.
[0169] After measurement, the ion exchange capacity (IEC) of the obtained composite proton membrane is 0.96 mmol / g; and the ion conductivity of the composite proton membrane is 65 mS / cm.
[0170] In the composite proton membrane, the mass fraction of the perfluorosulfonic acid ion polymer A2 is 10%.
[0171] Example 8
[0172] A fuel cell composite proton membrane of a perfluorosulfonic acid polymer with a triazole group and a preparation method thereof, comprising the following steps:
[0173] (1) The target product A2 obtained in Example 1 was dissolved in a mixed solvent of isopropanol / water (volume ratio = 8:2) to prepare a 20 wt % polymer solution A9.
[0174] (2) The perfluorosulfonic acid resin (V) in Example 7 was dissolved in a mixed solvent of isopropanol / water (volume ratio = 8:2) to prepare a 20 wt % polymer solution A10.
[0175] (3) Solution A9 was added to solution A10 and mixed evenly by mechanical stirring, with the mass ratio of the two being 3:7; the obtained mixed solution was coated on a clean and smooth quartz surface dish, pre-dried at 80° C., and then dried in an oven at 145° C. for 90 minutes, taken out and demolded, thereby preparing a long-life perfluorosulfonic acid composite proton membrane.
[0176] The IEC measurement showed that the ion exchange capacity (IEC) of the obtained composite proton membrane was 0.98 mmol / g.
[0177] The ionic conductivity of the composite proton membrane is 75 mS / cm.
[0178] In the composite proton membrane, the mass fraction of the perfluorosulfonic acid ion polymer A2 is 30%.
[0179] Example 9
[0180] The preparation of a membrane electrode for a free radical resistant fuel cell comprises the following specific steps:
[0181] (1) The resin (V) in Example 7 was dissolved in a mixed solvent of water / isopropanol (volume ratio of 2:8) to prepare a 5 wt% perfluorosulfonic acid resin solution, and then the target product A2 polymer in Example 1 was added to prepare a mixed solution, wherein the mass fraction of A2 in the obtained mixed solution was 15%, and then 10 mL of the mixed solution was added with a Pt / C catalyst, and ultrasonicated for 150 min to obtain a membrane electrode slurry, wherein the mass fraction of the polymer in the obtained slurry was 5%, and the mass ratio of A2 to V in the polymer was 3:7;
[0182] (2) coating the perfluorosulfonic acid resin solution in step (1) on a clean and smooth quartz surface dish, pre-drying at 80° C., drying in an oven at 145° C. for 90 minutes, removing from the mold, and preparing a proton membrane;
[0183] (3) The membrane electrode slurry of step (1) was sprayed onto the hydrophobic treated 2 cm×2 cm gas diffusion layer using a spray gun to form a catalyst layer. After heat treatment at 130°C for 90 min, the platinum loading on the catalyst layer surface was 0.4 mg / cm 2 , obtaining an electrode layer consisting of a gas diffusion layer and a catalyst layer, wherein the obtained electrode layer is divided into a hydrogen electrode and an oxygen electrode;
[0184] (4) Place the hydrogen electrode and oxygen electrode cut to appropriate sizes on the upper and lower sides of the proton membrane (3 cm×3 cm) in step (2), align them up and down and make sure they fit together perfectly, and then heat-press them using a press with a pressure of 0.8 MPa and a temperature of 140°C for 60 seconds. Open the press, cool naturally, and then take out the resulting membrane electrode for fuel cells.
[0185] Example 10
[0186] The preparation of a composite membrane electrode for a free radical resistant fuel cell comprises the following specific steps:
[0187] (1) The perfluorosulfonic acid resin V in Example 7 was dissolved in a water / isopropanol (volume ratio of 2:8) mixed solvent to prepare a 5 wt% perfluorosulfonic acid resin solution, and then the target product A2 polymer in Example 1 was added to prepare a mixed solution, and the mass fraction of A2 in the obtained mixed solution was 15%. Then, 10 mL of the mixed solution was added with a Pt / C catalyst, and ultrasonicated for 150 min to obtain a membrane electrode slurry. The mass fraction of the polymer in the obtained membrane electrode slurry was 5%, and the mass ratio of A2 to V in the polymer was 3:7.
[0188] (2) coating the mixed solution in step (1) on a clean and smooth quartz surface dish, pre-drying at 80° C., drying in an oven at 145° C. for 90 minutes, taking out and demolding, thereby preparing a composite proton membrane;
[0189] (3) The membrane electrode slurry of step (1) was sprayed onto the hydrophobic treated 2 cm×2 cm gas diffusion layer using a spray gun to form a catalyst layer. After heat treatment at 130°C for 90 min, the platinum loading on the catalyst layer surface was 0.4 mg / cm 2 , obtaining an electrode layer consisting of a gas diffusion layer and a catalyst layer, wherein the obtained electrode layer is divided into a hydrogen electrode and an oxygen electrode;
[0190] (4) Place the hydrogen electrode and oxygen electrode cut to appropriate sizes on the upper and lower sides of the composite proton membrane (3 cm×3 cm) prepared in step (2), align them up and down and make sure they fit together perfectly, and then heat-press them using a press with a pressure of 0.8 MPa, a temperature of 140°C, and a duration of 60 seconds. Open the press, cool naturally, and then take out the composite membrane electrode for fuel cells.
[0191] Comparative Example 1
[0192] The proton membrane is prepared using unmodified perfluorosulfonic acid resin (V) as raw material, and the specific steps are as follows:
[0193] The perfluorosulfonic acid resin (V) in Example 7 was dissolved in a mixed solvent of isopropanol / water (volume ratio = 8:2) to prepare a 20 wt% perfluorosulfonic acid resin solution without adding any additives. The resulting solution was coated on a clean and smooth quartz surface dish, pre-dried at 80° C., placed in an oven at 145° C. for 90 minutes, taken out and demolded to prepare an unmodified perfluorosulfonic acid proton membrane.
[0194] After IEC measurement, the IEC of the obtained proton membrane was 0.95mmol / g and the ionic conductivity was 60mS / cm.
[0195] Comparative Example 2
[0196] The membrane electrode is prepared using unmodified perfluorosulfonic acid resin (V) as raw material, and the specific steps are as follows:
[0197] (1) The perfluorosulfonic acid resin (V) in Example 7 was dissolved in a mixed solvent of isopropanol / water (volume ratio of 8:2) to prepare a 5 wt% perfluorosulfonic acid resin solution, and then 10 mL of the 5 wt% perfluorosulfonic acid resin solution was added to a Pt / C catalyst and ultrasonicated for 100 min to obtain a membrane electrode slurry, wherein the mass fraction of the polymer in the obtained slurry was 5%.
[0198] (2) coating a 5 wt % perfluorosulfonic acid resin solution in step (1) on a clean and smooth quartz surface dish, pre-drying at 80° C., drying in an oven at 145° C. for 80 minutes, removing the solution from the mold, and preparing an unmodified perfluorosulfonic acid proton membrane;
[0199] (3) The membrane electrode slurry of step (1) was sprayed onto the hydrophobic treated 2 cm×2 cm gas diffusion layer using a spray gun to form a catalyst layer. After heat treatment at 130°C for 90 min, the platinum loading on the catalyst layer surface was 0.4 mg / cm 2 , obtaining an electrode layer consisting of a gas diffusion layer and a catalyst layer, wherein the obtained electrode layer is divided into a hydrogen electrode and an oxygen electrode;
[0200] (4) Place the hydrogen electrode and oxygen electrode cut to appropriate sizes on the upper and lower sides of the proton membrane (3 cm×3 cm) in step (2), align them up and down and make sure they fit together perfectly. Then, heat press them with a press. The pressure of the press is 0.8 MPa, the temperature of the hot press is 140°C, and the duration is 60 seconds. Open the press, and take out the unmodified membrane electrode after natural cooling.
[0201] Comparative Example 3
[0202] The preparation of a proton membrane for a fuel cell and a membrane electrode for an anti-free radical fuel cell comprises the following specific steps:
[0203] 4-amino-3,5-di-2-pyridyl-4H-1,2,4-triazole was directly added as an additive to the perfluorosulfonic acid polymer solution A8, the molar ratio of 4-amino-3,5-di-2-pyridyl-4H-1,2,4-triazole to the perfluorosulfonic acid polymer in the mixed solution was about 1:9.8, the obtained mixed solution was coated on a clean and smooth quartz surface dish, and after pre-drying at 80°C, it was placed in an oven at 145°C for 90 minutes, and the mold was removed to prepare a proton membrane for a fuel cell, and the mass content of the additive was 0.5%. After measurement, the ion exchange capacity (IEC) of the obtained composite proton membrane was 0.90mmol / g. The ionic conductivity of the above composite proton membrane at room temperature (25°C) was 50.5mS / cm. The above proton membrane was used to prepare a membrane electrode and perform performance tests with reference to Comparative Example 2.
[0204] The perfluorosulfonic acid ionomer, proton membrane and membrane electrode prepared above were tested for performance, and the results are shown in Tables 1 to 3:
[0205] Table 1. Chemical stability test results of perfluorosulfonic acid ionomers with triazole groups and unmodified perfluorosulfonic acid polymers
[0206]
[0207]
[0208] As shown in Table 1, the IEC of the perfluoro ion polymer prepared by the present invention is above 94% after being tested by the Fenton test for 200 hours, and the thermal degradation temperature is also above 290°C. Compared with the unmodified perfluorosulfonic acid polymer, the IEC retention rate and thermal degradation temperature are significantly improved. This shows that the perfluorosulfonic acid ion polymer with triazole groups prepared by the present invention has high chemical stability, weakens or slows down the degradation of the polymer, and has sufficient mechanical strength and thermal stability.
[0209] Table 2. Performance test results of proton membrane
[0210]
[0211] As can be seen from Table 2, the proton membrane prepared by the perfluorosulfonic acid ion polymer with a triazole group of the present invention has an ion conductivity retention rate of more than 94% after being tested in the Fenton test for 200 hours, and the thermal degradation temperature of the proton membrane is more than 290°C; the composite proton membrane prepared by the perfluorosulfonic acid ion polymer with a triazole group of the present invention has an ion conductivity retention rate of more than 95% after being tested in the Fenton test for 200 hours, and the thermal degradation temperature of the composite proton exchange membrane is more than 280°C; compared with the proton membrane prepared by the perfluorosulfonic acid resin without modification (Comparative Examples 1 and 3), the chemical stability and thermal stability of the proton membrane of the present invention are significantly improved, and the service life of the proton membrane is effectively extended.
[0212] Table 3. Performance test results of membrane electrode
[0213]
[0214] As shown in Table 3, the membrane electrode prepared by the perfluoro ion polymer with triazole groups of the present invention can last for more than 200 hours at open circuit voltage (OCV), 30% relative humidity (RH) and 90°C, while the membrane electrode prepared by the unmodified perfluorosulfonic acid resin (Comparative Example 2) lasts for only 95.3 hours, and the membrane electrode prepared by directly adding 4-amino-3,5-di-2-pyridyl-4H-1,2,4-triazole to the conventional perfluorosulfonic acid polymer lasts for only 82.5 hours. This shows that the durability of the membrane electrode prepared by the present invention has been greatly improved.
Claims
1. A long-life proton exchange membrane with triazole groups, characterized in that: The components of the proton exchange membrane include a perfluoro ion polymer having a structure as shown in formula (I): Wherein, the structure of formula (I) includes (A) unit and (B) unit, (A) unit is a triazole structural unit, (A) unit includes a triazole group M and a perfluoroether structural unit, (B) unit includes an ionic group -SO3H and a perfluoroether structural unit; In the structure of formula (I), m is an integer from 0 to 10, and n is an integer from 1 to 6; In the structure of formula (I), x is an integer of 1-30, x+y / (x+y+z)=0.05-0.8, y / (y+z)=0.2-0.6; The number average molecular weight of the perfluorosulfonic acid ion polymer in formula (I) is 200,000 to 1,000,000; The structural formula of the reagent providing the triazole group M in the (A) unit is shown in formula (II), Among them, the R1 to R9 groups are any one of -H, -NH2, -PhNH2, -Cl, -Br, -PhCOOH, -CH3, -Ph (Ph represents a benzene ring), -O-CH3, and -NO2.
2. The long-life proton exchange membrane according to claim 1, characterized in that: m is an integer of 1 to 3, n is an integer of 1 to 3, x+y / (x+y+z)=0.15 to 0.4, y / (y+z)=0.2 to 0.4, and the number average molecular weight of the perfluorosulfonic acid ion polymer in formula (I) is 200,000 to 600,000; preferably, m=1, n=2, and the number average molecular weight of the perfluorosulfonic acid ion polymer in formula (I) is 300,000 to 500,000.
3. The long-life proton exchange membrane according to claim 1, characterized in that: In the R1 to R9 groups described in formula (II), the number of 1≤-NH2≤3, and the number of electron-withdrawing groups≤3.
4. The long-life proton exchange membrane according to claim 3, characterized in that: R1 is -H, -NH2, -PhNH2, -Cl, -Br, -PhCOOH, -CH3, -Ph or -O-CH3; R2 is -H, -NH2, -PhNH2, -Cl, -PhCOOH or -CH3; R3 is -H, -NH2, -PhNH2, -Br, -PhCOOH, -CH3 or -Ph; R4 is -H, -NH2, -PhNH2, -Br, -PhCOOH, -CH3 or -Ph; R5 is -H, -NH2, -PhNH2, -Br or -CH3; R6 is -H, -NH2, -PhNH2, -Cl, -Br, -CH3 or -O-CH3; R7 is -H, -NH2, -PhNH2, -Br, -CH3 or -NO2; R8 is -H, -NH2, -PhNH2, -Br, -CH3 or -NO2; R9 is -H, -NH2, -PhNH2, -Cl, -Br, -CH3 or -Ph; Preferably, R1 and R2 are independently one of -NH2, -H, and -PhNH2; R3 and R4 are independently one of -NH2, -H, -PhNH2, and -CH3; R5 and R8 are independently one of -H, -NH2, and -CH3; R6 and R9 are independently one of -H, -NH2, and -PhNH2; R7 is one of -H, -NH2, and -NO2; More preferably, R1 is -NH2, and R2 to R9 are all -H.
5. The long-life proton exchange membrane according to any one of claims 1 to 3, characterized in that: The preparation method of the perfluoro ion polymer comprises the following steps: (1) selecting a perfluorosulfonyl fluoride resin as described in Formula III and a reagent containing a triazole group M to undergo a one-step grafting reaction in an organic solvent to synthesize an intermediate product as described in Formula IV; Alternatively, the perfluorosulfonyl fluoride resin as shown in Formula III is pre-swelled in an organic solvent, and then a grafting reaction is carried out with a reagent containing a triazole group M to synthesize an intermediate product as shown in Formula IV; The reaction formula is as follows: (2) The intermediate product obtained in step (1) as shown in formula IV is treated with alkali and acid successively to complete ion exchange, and the unreacted sulfonyl fluoride group (-SO2F) is converted into a perfluorosulfonic acid group (-SO3H), and after washing and drying, a perfluorosulfonic acid ion polymer with a triazole group as shown in formula I is obtained. The reaction formula is as follows:
6. The method for preparing a long-life proton exchange membrane according to any one of claims 1 to 5, characterized in that: The following steps are involved: The perfluorosulfonic acid ion polymer with triazole groups is dissolved in an organic solvent to prepare a perfluorosulfonic acid ion polymer solution, and the perfluorosulfonic acid ion polymer solution is used to directly prepare a proton membrane; Alternatively, a perfluorosulfonic acid ion polymer with a triazole group as shown in formula (I) is added as a free radical quencher to a perfluorosulfonic acid resin solution to obtain a polymer composite solution, and the composite proton membrane is prepared using the polymer composite solution.
7. The method for preparing a long-life proton exchange membrane according to claim 6, characterized in that: The concentration of the perfluorosulfonic acid ion polymer solution is 2-35 wt%, preferably 5-30 wt%. Preferably, the total concentration of the polymer in the polymer composite solution is 5-30%.
8. The method for preparing a long-life proton exchange membrane according to claim 6, characterized in that: The organic solvent is at least one of N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, ethanol, isopropanol, ethanol / water mixed solvent, isopropanol / water mixed solvent, dimethyl sulfoxide or ethyl acetate.
9. The method for preparing a long-life proton exchange membrane according to claim 6, characterized in that: The volume ratio of ethanol to water in the perfluorosulfonic acid ion polymer solution is 8-9:1-2, and the volume ratio of isopropanol to water is 8-9:1-2.
10. The method for preparing a long-life proton exchange membrane according to claim 6, characterized in that: The steps of the solution casting method are: The perfluorosulfonic acid ion polymer solution or polymer composite solution is coated on a quartz surface dish, pre-dried at 80-90° C., dried at 140-150° C. for 90-100 minutes, and then removed from the mold.
Citation Information
Patent Citations
Method for improving chemical stability of proton exchange membrane
CN102479956A
High-tolerance perfluorinated proton membrane and preparation method thereof
CN112436170A